Intratumoral immunosuppression profiles in 11q‐deleted neuroblastomas provide new potential therapeutic targets. Issue 2 (19th January 2021) - Coronado, Esther; Yañez, Yania; Vidal, Enrique; Rubio, Luis; Vera‐Sempere, Francisco; Cañada‐Martínez, Antonio José; Panadero, Joaquín; Cañete, Adela; Ladenstein, Ruth; Castel, Victoria; Font de Mora, Jaime
Abstract : High‐risk neuroblastoma (NB) patients with 11q deletion frequently undergo late but consecutive relapse cycles with fatal outcome. To date, no actionable targets to improve current multimodal treatment have been identified. We analyzed immune microenvironment and genetic profiles of high‐risk NB correlating with 11q immune status. We show in two independent cohorts that 11q‐deleted NB exhibits various immune inhibitory mechanisms, including increased CD4+ resting T cells and M2 macrophages, higher expression of programmed death‐ligand 1, interleukin‐10, transforming growth factor‐beta‐1, and indoleamine 2, 3‐dioxygenase 1 ( P  < 0.05), and also higher chromosomal breakages ( P  ≤ 0.02) and hemizygosity of immunosuppressive miRNAs than MYCN‐amplified and other 11q‐nondeleted high‐risk NB. We also analyzed benefits of maintenance treatment in 83 high‐risk stage M NB patients focusing on 11q status, either with standard anti‐GD2 immunotherapy ( n  = 50) or previous retinoic acid‐based therapy alone ( n  = 33). Immunotherapy associated with higher EFS (50 vs. 30, P  = 0.028) and OS (72 vs. 52, P  = 0.047) at 3 years in the overall population. Despite benefits from standard anti‐GD2 immunotherapy in high‐risk NB patients, those with 11q deletion still face poor outcome. This NB subgroup displays intratumoral immune suppression profiles, revealing a potential therapeutic strategy with combination immunotherapy to circumvent this immune checkpoint blockade. Abstract : High‐risk 11q‐deleted neuroblastomas display features of a higher immunosuppression microenvironment than other high‐risk neruoblastomas. Efficacy of current anti‐GD2 immunotherapy in 11q‐deleted neuroblastomas may be reduced by inhibition of effector cells by kynurenine production and tryptophan depletion by IDO1, polarized M2 macrophages, PD‐L1 expression, and IL‐10‐dependent Treg conversion from resting CD4+ T cells, providing a rationale for further combination immunotherapy studies.